Oxyfunctionalisation of adamantane using inorganic-organic hybrid materials based on isopoly and heteropoly anions: kinetics and mechanistic studies - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2007)
{Oxyfunctionalisation of adamantane with 30% aq.H2O2 in butyronitrile solvent was efficiently catalyzed by inorganic-organic hybrid materials synthesized by the immobilisation of isopoly (WOx = sodium tungstate
Keywords: adamantane; inorganic-organic hybrid materials; oxyfunctionalisation; vanadium (V) superoxo intermediate